REVISI PERATURAN PEMERINTAH NOMOR 92 TAHUN 2015 TERHADAP KOMPONEN DAN BESARAN GANTI KERUGIAN - Rachmat Trijono (JURNAL ILMIAH LIVING LAW, 2019)
Compensation in Article 77 KUHAP is regulated further PP No. 27 of 1983 has been amended PP No. 92 of 2015. Amount of compensation in PP No. 92 of 2015 has increased, however, the impression of injustice cannot be eliminated considering that in various instances the amount of compensation is not in accordance with the magnitude of the loss that actually occurred by the victim. The problem is policy of revised PP 92 of 2015 on components and the amount of compensation ideally. The purpose of this study is to find out and analyze the policy of revised PP 92 of 2015. This study used normative and sociological methods with qualitative approaches. This study used secondary and primary data. The results of the study: 1. The component of compensation: Returns to its original state; To bear the costs incurred to restore to its original state, in the form of serious injuries and minor injuries; Providing certain compensation in the event that it cannot be returned to its original state; Provide compensation for the loss of opportunity that should be obtained. 2. The amount of compensation is adjusted to the components. Recommended that the judge determine the amount of the loss, so the victim does not need to file a claim for compensation.